Hereditary multiple osteochondromas - João R. Nunes-Pires; Violeta Florova; Teresa Alves-da Silva (Publicaciones Permanyer, 2024)
A three-year-old boy's mother reports the appearance of painless swelling at the right tibia's proximal end, with one year of evolution, without previous trauma or local/systemic inflammatory signs, namely fever or lymphadenopathy.